Sequence-defined oligo(ortho-arylene) foldamers derived from the benzannulation of ortho(arylene ethynylene)s. Issue 10 (14th July 2016) - Lehnherr, Dan; Chen, Chen; Pedramrazi, Zahra; DeBlase, Catherine R.; Alzola, Joaquin M.; Keresztes, Ivan; Lobkovsky, Emil B.; Crommie, Michael F.; Dichtel, William R.
Abstract : A Cu-catalyzed benzannulation reaction transforms ortho (arylene ethynylene) oligomers into ortho -arylenes. Abstract : A Cu-catalyzed benzannulation reaction transforms ortho (arylene ethynylene) oligomers into ortho -arylenes. This approach circumvents iterative Suzuki cross-coupling reactions previously used to assemble hindered ortho -arylene backbones. These derivatives form helical folded structures in the solid-state and in solution, as demonstrated by X-ray crystallography and solution-state NMR analysis. DFT calculations of misfolded conformations are correlated with variable-temperature 1 H and EXSY NMR to reveal that folding is cooperative and more favorable in halide-substituted naphthalenes. Helical ortho -arylene foldamers with specific aromatic sequences organize functional π-electron systems into arrangements ideal for ambipolar charge transport and show preliminary promise for the surface-mediated synthesis of structurally defined graphene nanoribbons.